Clinico-pathological profile of female breast cancer in Kashmir: an institutional experience - Gadda, Irfan Rasool; Ahmad, Shiekh Owais; Gadoo , Sadaf Shafi (International Journal of Research in Medical Sciences, 2023)
Background: Breast cancer is the most common cancer among women and one of the most important causes of death among them. The present study tries to evaluate the demographic, clinical, and pathological profile of female breast cancer patients in Kashmir Methods: This study was done in government medical college Srinagar, department of radiation oncology. A retrospective review of 84 patients of breast cancer treated between January 2021 and March 2023 was done. Results: A total of 84 patients were taken for this study. Most patients presented in the 4th and 5th decade of life with a mean age of 45.5± 8.58. 50% of the patients were having T2 followed by 19.04% having T4 and 16.66% having T1 while 14.28 % had T3 stage. 32.1% of patients were having N0 nodal status, 25.0% were having N3 followed by 23.80% had N1 and 19.04% had N2 nodal disease.52.38% were having stage II and 36.90% were having stage III and 4.76% were having stage IV. 85.71% were having invasive ductal carcinoma, 9.52% were having invasive lobular carcinoma and 4.76% were having medullary carcinoma. 23.80% of patients were Triple +, 27.38 % of patients were Triple Negative, 25.0% were ER+/ PR+. Conclusions: The incidence of female breast cancer was more in the age group of 41–50 years. Stage II was more followed by Stage III. The most common histopathology type was invasive ductal carcinoma. Triple negativity was seen more in our patients.